Chronic early life stress induced by limited bedding and nesting (LBN) material in rodents: critical considerations of methodology, outcomes and translational potential. (3rd September 2017) - Walker, Claire-Dominique; Bath, Kevin G.; Joels, Marian; Korosi, Aniko; Larauche, Muriel; Lucassen, Paul J.; Morris, Margaret J.; Raineki, Charlis; Roth, Tania L.; Sullivan, Regina M.; Taché, Yvette; Baram, Tallie Z.
Abstract: The immediate and long-term effects of exposure to early life stress (ELS) have been documented in humans and animal models. Even relatively brief periods of stress during the first 10 days of life in rodents can impact later behavioral regulation and the vulnerability to develop adult pathologies, in particular an impairment of cognitive functions and neurogenesis, but also modified social, emotional, and conditioned fear responses. The development of preclinical models of ELS exposure allows the examination of mechanisms and testing of therapeutic approaches that are not possible in humans. Here, we describe limited bedding and nesting (LBN) procedures, with models that produce altered maternal behavior ranging from fragmentation of care to maltreatment of infants. The purpose of this paper is to discuss important issues related to the implementation of this chronic ELS procedure and to describe some of the most prominent endpoints and consequences, focusing on areas of convergence between laboratories. Effects on the hypothalamic-pituitary adrenal (HPA) axis, gut axis and metabolism are presented in addition to changes in cognitive and emotional functions. Interestingly, recent data have suggested a strong sex difference in some of the reported consequences of the LBN paradigm, with females being more resilient in general than males. As both the chronic and intermittent variants of the LBN procedure have profound consequences on the offspring with minimal external intervention from the investigator, this model is advantageous ecologically and has a large translational potential. In addition to the direct effect of ELS on neurodevelopmental outcomes, exposure to adverse early environments can also have intergenerational impacts on mental health and function in subsequent generation offspring. Thus, advancing our understanding of the effect of ELS on brain and behavioral development is of critical concern for the health and wellbeing of both the current population, and for generations to come.